(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess changes in quality of life and patient satisfaction after abdominoplasty using the BODY-Q instrument. Phương pháp: Nghiên cứu mô tả theo dõi dọc được thực hiện trên 39 bệnh nhân nữ trưởng thành đã thực hiện phẫu thuật tạo hình thành bụng tại Khoa Phẫu thuật tạo hình & Thẩm mỹ, Bệnh viện Đại học Y Hà Nội. Bệnh nhân được đánh giá bằng bộ câu hỏi BODY-Q tại hai thời điểm: trước mổ và sau mổ 3-6 tháng. Dữ liệu về đặc điểm nhân khẩu học, kỹ thuật phẫu thuật, chăm sóc sau mổ, biến chứng và đánh giá sẹo được thu thập bổ sung. Methods: A longitudinal descriptive study was conducted on 39 adult female patients who underwent abdominoplasty at the Faculty of Plastic and Reconstructive Surgery, Hanoi Medical University Hospital. Patients were assessed using the BODY-Q questionnaire at two time points: preoperatively and 3-6 months postoperatively. Data on demographic characteristics, surgical technique, postoperative care, complications, and scar assessment were additionally collected. Results: The mean patient age was 38.3 ± 6.35 years, with a mean BMI of 23.5 ± 2.7 kg/m². All patients are indicated for abdominoplasty according to individual indications, which may include liposuction of the abdomen or surrounding areas. The average hospital stay was 4.9 days, compression garment use lasted approximately 80.6 days, and reported postoperative pain persisted for around 10.1 days. The most common complication was seroma (20.5%), with no major complications or mortality. Regarding scar assessment, 56.4% of patients rated the scar as visible but acceptable, while 20.5% reported well-hidden scars. BODY-Q scores significantly increased after surgery: abdominal satisfaction improved from 24.0 to 75.9; body image from 42.9 to 67.0; and sexual well-being from 58.8 to 71.2 (p < 0.01). Scores for psychological and social functioning remained high postoperatively. Conclusions: Abdominoplasty significantly improved quality of life and patient satisfaction across multiple domains. BODY-Q proved to be an effective tool for quantifying surgical outcomes from the patient’s perspective and should be considered for routine use in aesthetic surgical practice.